Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1186/1472-6920-11-70
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the operative experience of basic surgical trainees in Ireland using a web-based logbook

Abstract: BackgroundThere is concern about the adequacy of operative exposure in surgical training programmes, in the context of changing work practices. We aimed to quantify the operative exposure of all trainees on the National Basic Surgical Training (BST) programme in Ireland and compare the results with arbitrary training targets.MethodsRetrospective analysis of data obtained from a web-based logbook (http://www.elogbook.org) for all general surgery and orthopaedic training posts between July 2007 and June 2009.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 32 publications
1
11
0
3
Order By: Relevance
“…El Reino Unido dispone de un registro electró nico centralizado en la web http://www.elogbook.org, accesible a diferentes especialidades quirú rgicas (online y a travé s de dispositivos mó viles), de uso obligado por los residentes desde 2003, y controlado por el Real Colegio de Cirujanos de Edimburgo [8][9][10] . A diferencia del LIRQ, el eLogbook registra operaciones completadas y no procedimientos, lo que es considerado un punto dé bil en los trabajos realizados acerca de eLogbook, sin embargo, sí que tienen cuidado en registrar el nivel de participació n (p.…”
Section: Discusió Nunclassified
See 2 more Smart Citations
“…El Reino Unido dispone de un registro electró nico centralizado en la web http://www.elogbook.org, accesible a diferentes especialidades quirú rgicas (online y a travé s de dispositivos mó viles), de uso obligado por los residentes desde 2003, y controlado por el Real Colegio de Cirujanos de Edimburgo [8][9][10] . A diferencia del LIRQ, el eLogbook registra operaciones completadas y no procedimientos, lo que es considerado un punto dé bil en los trabajos realizados acerca de eLogbook, sin embargo, sí que tienen cuidado en registrar el nivel de participació n (p.…”
Section: Discusió Nunclassified
“…Los datos registrados sirven para generar informes individuales o globales, los cuales se revisan y comentan 2 veces al añ o, del mismo modo que realizamos en nuestro servicio. Actualmente, má s de 22.000 cirujanos del Reino Unido, de diferentes especialidades quirú rgicas, usan el eLogbook y hay registradas má s de 10 millones de intervenciones quirú rgicas [8][9][10] .…”
Section: Discusió Nunclassified
See 1 more Smart Citation
“…Given the practical nature of the specialty, competency in a new range of skills must be developed. The use of electronic logbooks to record clinical experience is well-established, both in anaesthesia and other procedure-based specialties (Watt JM, Watt WM, 1998) (Lonergan PE, Mulsow J, Tanner WA, Traynor O, Tierney S, 2011). Specific logbook targets have been developed in other jurisdictions, but do not currently exist for early anaesthesia trainees in Ireland.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that operating experience is one of the key factors that can be used to quantify and assess training. 5 Over a period of 2 weeks, we performed a survey of 228 elective operating lists throughout our training region, covering 11 hospitals and all elective orthopaedic specialties. During this time, 41 lists were not used or attended by a trainee when they should have been: 31 were not used owing to consultants or trainees being on leave, 7 owing to trauma workload in the trust leading to elective cancellations, and 3 for other reasons such as departmental audit meetings.…”
mentioning
confidence: 99%